Long-term outcomes of mechanical versus biological valve prosthesis in native mitral valve infective endocarditis - Malmberg Markus; Anttila Vesa; Rautava Päivi; Gunn Jarmo; Kytö Ville (United Kingdom, 2022)
Objectives. To study the long-term outcomes of mitral valve replacement with mechanical or biological valve prostheses in native mitral valve infective endocarditis patients.
Desing. We conducted a retrospective, nationwide, multicenter cohort study with patients aged ≤70 years who were treated with mitral valve replacement for native mitral valve infective endocarditis in Finland between 2004 and 2017.
Results. The endpoints were all-cause mortality, ischemic stroke, major bleeding, and mitral valve reoperations. The results were adjusted for baseline features (age, gender, comorbidities, history of drug abuse, concomitant surgeries, operational urgency, and surgical center). The median follow-up time was 6.1 years. The 12-year cumulative mortality rates were 36% for mechanical prostheses and 74% for biological prostheses (adj. HR 0.40; CI: 0.17-0.91; p = 0.03). At follow-up, the ischemic stroke had occurred in 19% of patients with mechanical prosthesis and 33% of those with a biological prosthesis (adj. p = 0.52). The major bleeding rates within the 12-year follow-up period were 30% for mechanical prosthesis and 13% for a biological prosthesis (adj. p = 0.29). The mitral valve reoperation rates were 13% for mechanical prosthesis and 12% for a biological prosthesis (adj. p = 0.50). Drug abuse history did not have a significant modifying impact on the results (interaction p = 0.51 for mortality and ≥0.13 for secondary outcomes).
Conclusion. The use of mechanical mitral valve prosthesis is associated with lower long-term mortality compared to the biological prosthesis in non-elder native mitral valve infective endocarditis patients. The routine choice of biological mitral valve prostheses for this patient group is not supported by the results.